(untitled) (Global Journal of Human-Social Science, 2018)
In all higher institutions where English is the medium of instruction students are expected to have minimum English competence to understand their subject matter during their study In order to help students to have the expected English language competence English medium teachers play a pivotal role If English medium teachers use appropriate English expressions throughout their lessons students may benefit a lot The main objective of this study was to investigate the perception of second and third year university students towards their English medium teachers English language usage while delivering their classes 172 second and third year Dilla University students were selected using simple random sampling technique to participate in this study Questionnaire interview and classroom observation were employed to collect data With regard to data analysis method both qualitative and quantitative were employed The findings of the study showed that second and third year students have positive attitude towards their English medium teachers English usage as a medium of instruction in English medium classes Majority of the students believe that their teachers are contributing in improving their students English language skills Positive aspects are favoring the use of English as a medium of instruction in other subject classes The result also indicates that significant numbers of English medium teachers are helping the students by facilitating positive environment to use English language for the classroom interaction Therefore the current study has been concluded with feasible recommendations